Man and his world in the concepts of S. Freud and K. Jaspers (Journal of Philosophy Culture and Political Science, 2018)
The article is devoted to problem of human essence in the concepts of S. Freud and K. Jaspers, logical approaches of psychoanalysis and existentialism. According to Freud human thinking is predetermined, human spiritual world is entirely subjected to the causal explanation, because the essence is its biological nature. Freud could not be able to regard human as a free being, since he did not consider him as a real reflection. Unlike Freud Karl Jaspers recognized freedom as essence of human, following in this respect to I. Kant’s doctrine. K. Jaspers claims that the human substance is not something already held that man is eternal incompleteness. However, according to Jaspers a person is free to the extent that he is close to God. According to Jaspers, if the explanation can implemented only through the indication of causal conditionality, but the comprehension and interpretation is possible through philosophical faith.Key words: freedom, Causa Sui, substance, consciousness, unconscious, way of being.